Molecular and Immune Correlates of PDCD1 (PD-1), PD-L1 (CD274), and PD-L2 (PDCD1LG2) DNA Methylation in Triple Negative Breast Cancer. Issue 8 (October 2021) - Ralser, Damian J.; Klümper, Niklas; Gevensleben, Heidrun; Zarbl, Romina; Kaiser, Christina; Landsberg, Jennifer; Hölzel, Michael; Strieth, Sebastian; Faridi, Andree; Abramian, Alina; Dietrich, Dimo
Abstract : Immune checkpoints are important targets in oncological therapy. Recent studies have proven efficacy of immune checkpoint inhibition (ICI) in treatment of triple negative breast cancer (TNBC). However, only a proportion of TNBC-patients benefit from ICI. Thus, current scientific efforts in this context are focused on the identification of a robust biomarker that enables patient stratification. In the present study, we investigated the epigenetic regulation of PD-1 ( PDCD1 ), PD-L1 ( CD274 ), and PD-L2 ( PDCD1LG2 ). Methylation data of PD-1, PD-L1, and PD-L2, and complex immunogenomic data were obtained from The Cancer Genome Atlas (TCGA). Methylation were systematically analyzed with regard to the transcriptional activity of the studied immune checkpoint genes and the tumor microenvironment. We found differential methylation of PD-1, PD-L1, and PD-L2 in normal adjacent tissue and TNBC tumor tissue. In the TNBC-TCGA cohort, methylation status of PD-1, PD-L1, and PD-L2 were significantly correlated with mRNA levels indicating a strong epigenetic regulation of the transcriptional activity. Moreover, PD-1, PD-L1, and PD-L2 methylation status was strongly associated with a distinct immune cell infiltration pattern. Our results indicate an epigenetic regulation of immune checkpoint genes through DNA methylation in TNBC. In addition, the methylation status was associated with a distinct composition of the tumor microenvironment. Overall, this provides a strong rationale for assessing the value of PD-1, PD-L1, and PD-L2 DNA methylation to predict response to ICI and immunogenicity in TNBC.